2013
DOI: 10.1371/journal.pone.0062813
|View full text |Cite
|
Sign up to set email alerts
|

Site Fidelity in Space Use by Spider Monkeys (Ateles geoffroyi) in the Yucatan Peninsula, Mexico

Abstract: Animal home ranges may vary little in their size and location in the short term but nevertheless show more variability in the long term. We evaluated the degree of site fidelity of two groups of spider monkeys (Ateles geoffroyi) over a 10- and 13-year period, respectively, in the northeastern Yucatan peninsula, Mexico. We used the Local Convex Hull method to estimate yearly home ranges and core areas (defined as the 60% probability contour) for the two groups. Home ranges varied from 7.7 to 49.6 ha and core ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 49 publications
(61 reference statements)
2
44
2
1
Order By: Relevance
“…Recent studies examining home range stability within primates have focused on the role of resource distribution [Asensio et al, 2012;Ramos-Fernandez et al, 2013;Wallace, 2006] and individual knowledge of the home range [Brockelman, 2009;Janmaat et al, 2009]. For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies examining home range stability within primates have focused on the role of resource distribution [Asensio et al, 2012;Ramos-Fernandez et al, 2013;Wallace, 2006] and individual knowledge of the home range [Brockelman, 2009;Janmaat et al, 2009]. For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013]. Furthermore, it has been argued that home range stability may be maintained due not only to the predictability of food resources but also the benefits of spatial information in general, including knowledge of efficient travel routes, safe escape routes, and relationships with neighboring conspecifics [Bartlett, 2002;Fuentes, 2000;Janmaat et al, 2009;Wallace, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…As spider monkeys have home ranges that are usually smaller than 170 ha [e.g., Chaves et al, 2011a;Di Fiore & Campbell, 2007;Fedigan et al, 1988;Wallace, 2008], we predict that the scale of effect for most response variables and landscape attributes will be lower than 170 ha. This is because the diet and behavior of primates are expected to be more strongly affected by habitat characteristics within their home range (e.g., food availability) than by spatial attributes of the areas located outside their home ranges [Arroyo-Rodríguez et al, 2013;Asensio et al, 2012a,b;Ramos-Fernández et al, 2013]. Also, because this is a forest-dependent species, we predict that all response variables will be more strongly related to differences in landscape forest cover (a surrogate of habitat amount) than with fragmentation (i.e., number of forest patches in the landscape) or patch isolation [Fahrig, 2003[Fahrig, , 2013, being this pattern consistent across several spatial scales [Fahrig, 1998;Smith et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…We used a novel site fidelity index that adds to the graphical method of Ramos-Fernandez et al [2013], as it quantifies fidelity, allowing comparison between species or groups and also between different periods. The site fidelity index may also be useful to investigate habitat use, allowing one to associate different habitat types with the degree to which particular areas are re-used.…”
Section: New Methods For Estimating Site Fidelity and Range Sizementioning
confidence: 99%
“…Because Ramos-Fernandez et al [2013] method consists mostly of a visual assessment tool, we created an index to quantify its estimation of site fidelity. This index is based on the region size and the number of times that it is reused over time steps (i.e., months or days in our study).…”
Section: Home Range and Core Area Fidelitymentioning
confidence: 99%